ETP-46321, a dual p110?/? class IA phosphoinositide 3-kinase inhibitor modulates T lymphocyte activation and collagen-induced arthritis (2016)
Class IA phosphoinositide 3-kinases (PI3Ks) are essential to function of normal and tumor cells, and to modulate immune responses. T lymphocytes express high levels of p110? and p110? class IA PI3K. Whereas the functioning of PI3K p110? in immune and autoimmune reactions is well established, the role of p110? is less well understood. Here, a novel dual p110?/? inhibitor (ETP-46321) and highly specific p110? (A66) or p110? (IC87114) inhibitors have been compared concerning T cell activation in vitro, as well as the effect on responses to protein antigen and collagen-induced arthritis in vivo. In vitro activation of naive CD4+ T lymphocytes by anti-CD3 and anti-CD28 was inhibited more effectively by the p110? inhibitor than by the p110? inhibitor as measured by cytokine secretion (IL-2, IL-10, and IFN-?), T-bet expression and NFAT activation. In activated CD4+ T cells re-stimulated through CD3 and ICOS, IC87114 inhibited Akt and Erk activation, and the secretion of IL-2, IL-4, IL-17A, and IFN-? better than A66. The p110?/? inhibitor ETP-46321, or p110? plus p110? inhibitors also inhibited IL-21 secretion by differentiated CD4+ T follicular (Tfh) or IL-17-producing (Th17) helper cells. In vivo, therapeutic administration of ETP-46321 significantly inhibited responses to protein antigen as well as collagen-induced arthritis, as measured by antigen-specific antibody responses, secretion of IL-10, IL-17A or IFN-?, or clinical symptoms. Hence, p110? as well as p110? Class IA PI3Ks are important to immune regulation; inhibition of both subunits may be an effective therapeutic approach in inflammatory autoimmune diseases like rheumatoid arthritis.